Tribology of polymer composites : characterization, properties, and applications - Rangappa, Sanjay Mavinkere; Siengchin, Suchart; Parameswaranpillai, Jyotishkumar; Friedrich, Klaus, 1945- (Elsevier series on tribology and surface engineering., 2020)
Tribology of Polymer Composites: Characterization, Properties, and Applications provides an exhaustive overview of the latest research, trends, applications and future directions of the tribology of polymer composites. Covering novel methods for the synthesis of polymer composites and their properties, the book starts by reviewing the fabrication techniques, wear and frictional properties of polymer composite materials. From there, it features chapters looking at the tribological behavior and properties of specific polymer composite materials such as synthetic fiber-reinforced, cellulose fiber-reinforced, wood fiber, synthetic fiber, mineral fiber-reinforced, and thermosetting composites. Final chapters cover the tribology of polymer nanocomposites and particulate polymer composites and their metal coatings. Applied examples spanning a wide range of industries are emphasized in each chapter.